Monetary and Fiscal Policy on Inflation in Indonesia: Threshold Vector Autoregression Approach - Lilis Yuliati; Badara Shofi Dana; Ati Musaiyaroh (Media Ekonomi dan Manajemen, 2025)
The combination of monetary and fiscal policies is used to stabilize prices in Indonesia. The purpose of this study is to analyse the role of monetary and fiscal policies in stabilizing prices in Indonesia through the threshold concept. The data used is time series (2013Q1-2023Q2) with the Threshold Vector Autoregression method. The results show that the interest rate and budget thresholds can affect inflation stability. Other variables, such as the exchange rate, output gap, and FFR, have varying effects depending on the threshold. Thus, combining adjustments in monetary and fiscal policies and understanding the impact of inflation at various policymakers can better manage economic growth and maintain price stability in the long term.